Analisis Awal Gerak Butiran Pada Transport Sedimen Tanah Gambut Pesisir Pulau Bengkalis - Refri Fadillah; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Abrasion and sedimentation are events that usually arise due to the movement and accumulation of material carried by ocean currents. Severe damage occurred in coastal areas such as on Bengkalis Island. Research on the initial motion of grains, especially on peat material, is very interesting to study. This study aims to analyze the relationship between flow velocity and grain diameter at the beginning of the movement of peat material grains. The initial motion of the peat material will be compared with the movement of the sand material. Modeling to analyze the initial motion of the grains on peat soil using Armfield Sediment Transport Demonstration Channel as flume. The flume velocity was varied starting from the lowest and symbolized by U, namely 1-7 (U=0.009890.10112 m/s) speed for peat material, and 4-10 (U=0.03973-0.18900 m/s) speed for sand material. The results showed that peat material experienced easier grain movement than sand material. This is due to the smaller spesific gravity of peat than sand. Proven based on the shield graph, the results of the critical shear stress on the sand sample No. 10 is below the shield graph, and on the peat material No. 10 is above the shield chart. Based on visual observations on peat sediments, it is found that the movement starts from the type of laminar flow, while in the sand sediments there is movement in the type of turbulent flow. Keywords : peat, flow velocity, initial motion, critical shear stress, shield graphic